Vacuum brazing of titanium alloy to stainless steel enhance by fiber laser surface texturing - Sulaiman H., A. J.; Aiman, M. H.; Ishak, M.; Quazi, M. M.; Zaharinie, T.; Ariga, T. (Faculty Mechanical Engineering, UMP, 2021)
A method for improving the brazing joining strength of Titanium alloy/Stainless steel fabricated through fibre laser surface texturing is introduced because it is a simple process that does not require the fabrication of complicated interlayers. However, previous research shows that a milimeter scale was fabricated by surface modification for dissimilar brazing join, yielding insignificant results and limiting the application and degree of enhancement. Fiber laser ablation was used in this study to create microscale periodic patterns (grooves) on a stainless steel surface. No defect or damage induced during laser surface texturing process. The groove dimension was tunable by controlling the laser parameters. Vacuum brazing of Ti6Al4V to 316L stainless steel with surface texturing, the average joint strength was 22.1 MPa, 34% of increase of joining strength compared to unprocessed flat surface. The combination of laser surface texturing and brazing proven effectively on joining strength enhancement.